Implementation of the one-year Early Childhood Education (ECE) policy: A review of the education implementation process - Naning Sulistyowati; Edi Waluyo; Diana (Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
Policy, as a set of regulations governing societal life, is analysed through three main aspects: effectiveness, efficiency, and fairness in implementation. Given the strategic role of ECE in supporting early childhood development as mandated by Indonesian Law No. 20 of 2003, adjusting the one-year ECE policy is crucial to achieving sustainable development goals. The transition from ECE to elementary education requires optimal support from teachers and parents, despite challenges arising from some ECE educators not yet meeting the expected qualifications. This study aims to describe the impacts, analyse the influencing factors, and examine the role of relevant institutions in the implementation of the one-year Early Childhood Education (ECE) policy in Semarang City. This study employs a descriptive, qualitative approach, using interviews and observations, to gain an in-depth understanding of policy implementation. Primary data were collected through direct interviews with school principals and educators, while secondary data were obtained from various relevant written sources. The findings indicate that the implementation of the one-year ECE policy in Tembalang District, Semarang City, significantly contributes to improving the quality of early childhood education. This policy supports inclusive education and expands equitable access to education. The success of the policy largely depends on teacher training, the availability of adequate facilities, and active parental involvement; thus, maintaining consistency in its implementation is essential to minimise the risk of programme failure.